If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(3x + 5y) = 0 (3x * 7 + 5y * 7) = 0 (21x + 35y) = 0 Solving 21x + 35y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-35y' to each side of the equation. 21x + 35y + -35y = 0 + -35y Combine like terms: 35y + -35y = 0 21x + 0 = 0 + -35y 21x = 0 + -35y Remove the zero: 21x = -35y Divide each side by '21'. x = -1.666666667y Simplifying x = -1.666666667y
| 15+3y=21 | | 2h+5=4h-9 | | 20x-10/5 | | x/-3=-6-(-4) | | 2x(2x/7)=(x/2)+(17/2) | | 3=-6(-4) | | 3(v+2)-v=2(v-1)+5 | | 4u=48 | | 3(w+2)+w=4(w-1)+10 | | (7x-5)(3x+3)= | | 77=11m | | (7x-5)(3x+3) | | m=1/2,b=0 | | 12p=60 | | 9x_=99 | | -7x^2+2x-3=0 | | 3x2x=24 | | 2x-2x/7=x/2+17/2 | | 60=12p | | 3m+17=6m+2 | | 3/4+-12 | | 12-a=25 | | -2/3r+2r=6/5r+14/5 | | -(9x+12)-4x | | 3(6z-1)-2(z+1)=5(z+1) | | 2(3n–5)+4=15–(9n–4) | | 6m+2=3m+17 | | 23+87*67= | | 60=(.4)*X | | a/12=7 | | [x-6]-7-3 | | 60=.4*x |